Household Food Security Analysis Pre And Post The Covid-19 Pandemic In Bengkulu Province - Wibowo, hariz; Ifebri, Rihan; Fauzi, Ariffatchur (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Bengkulu Province is one of the provinces that experienced changes in the food security index pre and post the pandemic Covid-19. In 2018, the food security index (IKP) for Bengkulu Province was 70.77 and will decrease in 2022 to 68. Even though the IKP has decreased, Bengkulu Province is still in the food secure category. The aim of this research is to find out whether there are differences in food security conditions at the household level pre and post the pandemic Covid-19 using descriptive analysis and formal tests. The results of the analysis using the chi-square test show that the Pearson chi-square test shows a significance value of 0.00 (<α=5%). This demonstrates that the year and the food security of a household are related. In accordance with the initial assumption that the pandemic Covid-19 occurred in 2020 and 2018-2019 was the year before the pandemic and 2021-2022 was after the pandemic, it can be concluded that reject H0 where a connection between the impact of the pandemic Covid-19 and household food security. This is in line with the previous descriptive analysis where there was a relationship between the Covid-19 pandemic and household food security